The split subject of 'Russian' history in A Disgraceful Affair – Skverny Anekdot. - Ascroft, Edward (Studies in East European Thought, 2025)
This article situates Dostoevsky's short story A Disgraceful Affair in a Lacanian, psychoanalytic context in order to interrogate Bakhtin's reading of Dostoevsky's poetics through his concepts of the 'carnivalesque', the 'chronotope', and the 'threshold'. Focusing on 'shame' and 'repetition' as functions of Otherness in this story, it will analyse the aesthetic means by which Dostoevsky constructs a 'new' pathological subject. It argues that in this neglected short story Dostoevsky's protagonist can be analysed much like the 'subjects' of poststructuralism, creating a split subject of 'Russian' history.